Gas-phase structure and reactivity of the keto tautomer of the deoxyguanosine radical cation1. Issue 39 (21st October 2015) - Feketeová, Linda; Chan, Bun; Khairallah, George N.; Steinmetz, Vincent; Maître, Philippe; Radom, Leo; O'Hair, Richard A. J.
<x xml:space="preserve">Abstract</x> Gas-phase IR spectroscopy, ion–molecule reactions, collision-induced dissociation and computational chemistry in combination form a powerful tool to gain insights into the structure of one-electron oxidised guanine in DNA and its resultant chemistry.